The Effect of Consumer Self-Confidence, Attitude Towards Paid Internet Advertising, and Continuance Search Intention on App-Purchase Decision - Fransiska Marieta Dwitasari; Margaretha Pink Berlianto (Publikasi Indonesia, 2024)
Paid internet advertising has been widely used in various industries including the healthcare industry. The number of customers using mobile healthcare applications to buy products or services also continues to grow. One of the healthcare applications that is widely used in Indonesia is Halodoc. Purpose: This research aims to study the structural relationship of consumer self-confidence to the app-purchase decision in Halodoc application, using indicators of attitudes towards paid internet advertising, perceived intrusiveness, and continuance search intentions on the internet. Methods: A total of 309 samples were obtained from consumers who had seen Halodoc application advertisements on the internet and had used Halodoc application to purchase products or services provided by the application at least once. Measurements were carried out using PLS-SEM to see the structural relationship between the indicators. Results: Consumer self-confidence has a positive effect towards paid internet advertising (t=7.614, p=0.000), continuance search intention (t=10.009, p=0.000), and app-purchase decision (t=19.972, p=0.000). Consumer self-confidence has no negative impact on perceived intrusiveness (t=1.564, p=0.059). Conclusion: This study shows that consumer self-confidence has a positive effect on attitudes towards paid internet advertising, continuance search intentions, and app-purchase decisions on mobile application.